Metabolite Changes in the Aqueous Humor of Patients With Retinal Vein Occlusion Macular Edema: A Metabolomics Analysis - Xiong, Xiaojing; Chen, Xu; Ma, Huafeng; Zheng, Zheng; Yang, Yazhu; Chen, Zhu; Zhou, Zixi; Pu, Jiaxin; Chen, Qingwei; Zheng, Minming (Frontiers in Cell and Developmental Biology, 2021)
Macular edema (ME) is the main cause of visual impairment in patients with retinal vein occlusion (RVO). The degree of ME affects the prognosis of RVO patients, while it lacks objective laboratory biomarkers. We aimed to compare aqueous humor samples from 28 patients with retinal vein occlusion macular edema (RVO-ME) to 27 age-and-sex-matched controls by ultra-high-performance liquid chromatography equipped with quadrupole time-of-flight mass spectrometry so as to identify the key biomarkers, and to increase the understanding of the mechanism of RVO-ME at the molecular level. Through univariate and multivariate statistical analysis, we identified 60 metabolites between RVO-ME patients and controls, and 40 differential metabolites in mild RVO-ME (300 μm ≤ central retinal thickness (CRT) < 400 μm) patients compared with severe RVO-ME (CRT ≥ 400 μm). Pathway enrichment analysis showed that the valine, leucine and isoleucine biosynthesis, ascorbate and aldarate metabolism and pantothenate and coenzyme A biosynthesis was significantly altered in RVO-ME in comparison with controls. Compared with mild RVO-ME, degradation and biosynthesis of valine, leucine and isoleucine, histidine metabolism, beta-alanine metabolism and pantothenate and coenzyme A biosynthesis were significantly changed in severe RVO-ME. Furthermore, the receiver operating characteristic (ROC) curve analysis revealed that adenosine, threonic acid, pyruvic acid and pyro-L-glutaminyl-L-glutamine could differentiate RVO-ME from controls with an area under the curve (AUC) of > 0.813. Urocanic acid, diethanolamine, 8-butanoylneosolaniol, niacinamide, paraldehyde, phytosphingosinehad, 4-aminobutyraldehyde, dihydrolipoate and 1-(beta-D-ribofuranosyl)-1,4-dihydronicotinamide had an AUC of > 0.848 for distinguishing mild RVO-ME from severe RVO-ME. Our study expanded the understanding of metabolomic changes in RVO-ME, which could help us to have a good understanding of the pathogenesis of RVO-ME.